ANALISA TERMODINAMIKA EVOLUSI MAGMA PADA PEMBENTUKAN KOMPLEK OFIOLIT KARANGSAMBUNG UTARA, JAWA TENGAH ( MODEL KRISTALISASI MAGMA ) - RACHMAT PRAWIRADINATA, AMAR
The dependence of chemical equilibrium constant on temperature, pressure and composition, is expressed by equation In K = a/T-b . The separation of solid phase from liquid phase in the fractional crytallization proces, can be explained by Rayleigh's law : / C = F ( D 1 ). Both relationship are C liquide solid used as basic calculation on the study of the magmatic evolution on the genesis of gabro, diabase and basalt of the North Karangsambung ophiolite, Central Java. Chemical analyses data of 20 mafic rock samples are used to understand more detail the above evolution processes.